Strategi Pemasaran Roasted Bean Kopi Arabika (Coffea Arabika) di Unit Usaha Pengolahan (UUP) Catur Paramitha Desa Catur Kabupaten Bangli Provinsi Bali - PRATAMA, YOGA; WIJAYANTI, PUTU UDAYANI; DEWI, IDA AYU LISTIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2023)
Marketing Strategy Roasted Bean Arabica (Coffea Arabica) in Unit Usaha Pengolahan (UUP) Catur Paramitha, Catur Village, Kintamani District, Bali. Coffee is one of the most widely grown crops and is a product that is in great demand in Indonesia. The growth and development of coffee enthusiasts makes coffee a promising business with considerable profits. Catur Kintamani Village is a village located in Bangli Regency which is the center of Kintamani Arabica coffee plantation and processing. Marketing strategy is a combination of activities that are planned and implemented in accordance with company decisions. This study aims to identify and identify internal environmental factors and external environmental factors owned by the UUP. Catur Paramitha who then set an alternative marketing strategy for Kintamani Arabica roasted coffee beans. The results of the data obtained through interviews, observation, and documentation. The informants consist of three internal informants who are in the UUP internal environment. Chess Paramitha and five informants are in the external environment. Analysis of the data used is the IFAS Matrix, EFAS Matrix, IE Matrix and SWOT Matrix. The results showed that there were four internal environmental factors, four strengths and four weaknesses. While the external environmental factors there are four opportunity factors and three threat factors. The results of the IFAS and EFAS matrix calculations show UUUP. Catur Paramitha in the IE matrix is in position II (growth and build) and the SWOT matrix is in Quadrant 1 (2.723: 3.134) which is an SO strategy in the SWOT diagram by maintaining product quality for market expansion and utilizing technology in the production business as well as expanding the marketing network of roasted beans, arabica coffee.